Cervical cancer prevention program in Nepal: a ‘training of trainers’ approach - Samantha Batman; Madan Piya; Sandhya Chapagain; Poonam Lama; Pabitra Maharjan; Binod Aryal; Maya Neupane; Shashwat Pariyar; Natacha Phoolcharoen; Vanessa Eaton; Vanessa Sarchet; Megan Kremzier; et al. (Journal of Global Health Reports)
# Background